State Behaviour in Arms Control: Is Canada a Rational State? - Alshammari, Mariam (Université d'Ottawa | University of Ottawa, 2015)
A thorough discussion of Canada’s previous behaviours in arms control will be discussed in an effort to emphasize precedents and how they are not followed. The paper’s goal to assess two separate case studies, anti-personnel landmines and cluster munitions, results in a conclusion that Canada follows an irrational behavioural model. The use of Graham Allison’s theory of governance, coupled with Philippe Lagasse’s idea of a two track approach, is the means through which this conclusion was made. Finally, the paper determines that Canada can benefit more greatly by accepting this conclusion and using it as a means of drafting a concrete defence strate-gy that will allow for the manipulation of different tools, such as the two track approach. In this way, Canada will be seen as a more transparent state and will not need to defend its need to oc-casionally break free from precedent.